To switch or not to switch: should the updated Intergroup Exemestane Study alter our decision?. Issue 1 (January 2008) - Iddon, Julie; Bundred, Nigel J
Adjuvant therapy for breast cancer with aromatase inhibitors improves survival compared with tamoxifen; however, whether they should be given upfront or sequentially after 2–3 years of tamoxifen in estrogen receptor-positive early breast cancer affecting postmenopausal women is unclear. The Intergroup Exemestane Study looked at 4724 postmenopausal patients with estrogen receptor-positive or unknown breast cancer who had been disease free for 2–3 years on tamoxifen and were randomly assigned to switch to exemestane or to continue tamoxifen for the remainder of a 5-year endocrine treatment period. A significant disease-free survival advantage (p = 0.0001) was seen in favor of exemestane, with an absolute benefit of 3.3% by the end of treatment. This trial is the first to show an overall survival advantage for switching in estrogen receptor-positive breast cancer (p≤ 0.05). In total, 222 deaths occurred in the exemestane group compared with 261 deaths in the tamoxifen group, with a hazard ratio of 0.8 (95% confidence interval: 0.71–1.02; p = 0.08). A retrospective exclusion of patients who had estrogen receptor-negative disease improved the adjusted hazard ratio to 0.85 (0.69–1.0; p = 0.05). Contralateral breast cancer was reduced by 50% both in intention-to-treat and estrogen receptor-positive groups. These results indicate that a similar overall reduction in recurrence can be achieved with a switching or an upfront aromatase inhibitor strategy, but with a reduction in the overall morbidity. The 5% of early breast cancer patients who relapse in the first 2 years of tamoxifen treatment can be identified from 10% of the overall population. The remaining 90% could switch after 2–3 years. Controversy remains regarding whether switching is the optimal strategy and will only be resolved following the results of the Breast International Group 1-98 trial involving sequential therapy. Switching to exemestane for patients who have already had tamoxifen therapy for 2–3 years would appear to be an appropriate strategy for the majority of early breast cancer patients.